Research on water floaters collection system based on Faraday waves - Zhang Xinjian; Bi Yan; Lu Yanmin; Wu Yanping; Yang Jiajun; Yang Weihong; Fan Juan (Dianzi Jishu Yingyong, 2022)
In order to improve living conditions in the town and solve the problems from garbage floaters on small-area water surface in landscape zones, this article, based on Faraday waves theory, designs a small-area water floaters collection automatic system device, which is consist of vibration source(to produce Faraday waves), floating platform and collecting device. This device utilizes single chip to output specific frequencies to the floating platform, and then makes the floaters which connected the floating platform to clap the water surface in order to produce waves in corresponding wavelength. This device is able to grab long-distance granules floaters on water surface. Under Faraday waves′ characteristic effect, granules floaters on water surface will move to a certain place according to relevant track, as a result, it is convenient for collecting device to salvage and recycle water surface garbage. This research result is able to collect granules floaters on small-area water surface without any second harm to the organism in the water. It is an economic, environment-friendly innovation.